Peran Guru Tafsir Amaly Dalam Peningkatan Sikap Spiritual Siswa Di MTs Al-Urwatul Wutsqo Jombang - Fadlilah Najahiyah; Siti Zuliani (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
Al-Quran is a way of life for every human being, especially for Muslims who are the book of teachings. Al-Quran is not just to be read, but also practiced in everyday life, while to understand and practice the knowledge of the Koran definitely requires guidance from the teacher so as not to misunderstand and practice the Koran. Al-Quran teachers play an important role in improving spiritual attitudes. The purposes of this study are 1) To describe the role of the Tafsir Amaly in improving the spiritual attitudes of students in class VIII A MTs Al-Urwatul Wutsqo Jombang 2) To describe the spiritual attitudes of students in class VIII A MTs Al-Urwatul Wutsqo Jombang 3) To describe the supporting factors and inhibiting the role of Amaly in improving the spiritual attitude of students in class VIII A MTs Al-Urwatul Wutsqo Jombang. This research is a qualitative field research, the form of the research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that: 1) The teacher's role in improving the spiritual attitude of class VIII A students focused on four roles, namely: as role models, teachers, mentors, and motivators. 2) Spiritual attitudes in class VIII A MTs Al-Urwatul Wutsqo Jombang, focused on three forms of spiritual attitudes, namely: a) piety b) strong faith c) quality of worship. And 3) the supporting and inhibiting factors of Amaly in improving the spiritual attitude of the students of MTs al-Urwatul Wutsqo Jombang there are two categories, namely internal and external factors, internal supporting factors in the form of lust, while external factors are: a) environment b) customs c ) imtaqisasi, the internal is lust, while external background broken home.